2020
DOI: 10.1101/2020.07.02.184754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cocaine-dependent acquisition of locomotor sensitization and conditioned place preference requires D1 dopaminergic signaling through a cyclic AMP, NCS-Rapgef2, ERK and Egr-1/Zif268 pathway

Abstract: ABSTRACTElucidation of the underlying mechanism of dopamine signaling to ERK that underlies plasticity in dopamine D1 receptor expressingneurons leadingto acquired cocaine preference is incomplete. NCS-Rapgef2 is a novel cAMP effector, expressed in neuronal and endocrine cells in adult mammals, that is required for D1 dopamine receptor-dependent ERK phosphorylation in mouse brain. In this report, we studied the effects of abrogating NCS-Rapgef2 expression on cAMP-dependent ERK→… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Both floxed and cKO mice could distinguish between training and novel contexts (Figure 2C 2 , Two-way ANOVA followed by post hoc Bonferroni t-test, context effect: F (1, 82) =66.802, p<0.001). Although RapGEF2 is ablated in BLA in cKO mice (Jiang et al, 2017, 2021), these mutant mice associate tone with the foot shock as did the floxed control mice, and did not differ from floxed controls in cued fear memory when tested 24 h after fear conditioning (Figure 2C 3 , Two-way ANOVA followed by post hoc Bonferroni t-test, to compare floxed and cKO mice during tone presentation. Conditioning effect: F (1, 82) =189.502, p<0.001; genotype effect: F (1, 82) =0.462, p=0.499; flox vs cKO after conditioning, p=0.351).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Both floxed and cKO mice could distinguish between training and novel contexts (Figure 2C 2 , Two-way ANOVA followed by post hoc Bonferroni t-test, context effect: F (1, 82) =66.802, p<0.001). Although RapGEF2 is ablated in BLA in cKO mice (Jiang et al, 2017, 2021), these mutant mice associate tone with the foot shock as did the floxed control mice, and did not differ from floxed controls in cued fear memory when tested 24 h after fear conditioning (Figure 2C 3 , Two-way ANOVA followed by post hoc Bonferroni t-test, to compare floxed and cKO mice during tone presentation. Conditioning effect: F (1, 82) =189.502, p<0.001; genotype effect: F (1, 82) =0.462, p=0.499; flox vs cKO after conditioning, p=0.351).…”
Section: Resultsmentioning
confidence: 97%
“…The dynamic changes of expression of immediate-early genes (IEGs), such as c-Fos and Egr-1, have been widely used as molecular markers for neuronal plastic changes measured in cell culture (Harada et al, 2001; Han et al, 2007; Adams et al, 2017) and in vivo ((Jiang et al, 2021) and references therein), especially in the context of genetic manipulation of hippocampal function required for memory formation (Liu et al, 2012; Ramirez et al, 2013; Liu et al, 2014; Gallo et al, 2018). Previous studies suggested that most neuronal ensembles encoding fear memory may simultaneously express various IEGs, however, to what extent IEG-positive ensembles overlap with each other and whether they are regulated separately in the same neurons, remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations